Modelowanie funduszu nadwyżkowego w ubezpieczeniach majątkowych - Wanat, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The European Commission is developing new rules (so-called Solvency II) for insurance companies. Under this concept, an insurer is allowed to verify its solvency by using an internal risk management model previously approved by regulatory authority. In this paper we presents such an internal approach for modelling the surplus process of non-life insurer. The proposed model uses a simulation technique and is based on dynamic financial analysis. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 320-328